2016
DOI: 10.1002/jcla.21867
|View full text |Cite
|
Sign up to set email alerts
|

Setup of a Protocol of Molecular Diagnosis of β‐Thalassemia Mutations in Tunisia using Denaturing High‐Performance Liquid Chromatography (DHPLC)

Abstract: Compared to other genotyping techniques, the DHPLC method can meet the requirements of direct genotyping of known β-thalassemia mutations in Tunisia and to be applied as a powerful tool for the genetic screening of prenatal and postnatal individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Two major differences were observed: First, all the β‐thalassemia major patients were homozygous or compound heterozygous for C39(C > T). Furthermore, it has been noticed that this variant, though the most common in all previous studies, showed a much higher frequency (71.15%) compared to those found in Morocco (15.56%–28.05%) (Agouti et al, 2007 ; Agouti, Badens, et al, 2008 ; Lemsaddek et al, 2003 , 2004 ), in Algeria (26%–43%) (Abdaoui et al, 2019 ; Bennani et al, 1994 ; Boudrahem‐Addour et al, 2009 ; Labie et al, 1990 ) and in Tunisia (49%–37.50%) (Chouk et al, 2004 ; Fattoum et al, 2004 ; Sahli et al, 2016 ). The second particularity in our result concern the three variants (FSC8(−AA), IVS‐I‐6(T > C), and IVS‐II‐745(C > G)) described in previous studies as three of the five most common variants in Morocco, are surprisingly absent in the Eastern region of Morocco and are rare in Algerian and Tunisian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two major differences were observed: First, all the β‐thalassemia major patients were homozygous or compound heterozygous for C39(C > T). Furthermore, it has been noticed that this variant, though the most common in all previous studies, showed a much higher frequency (71.15%) compared to those found in Morocco (15.56%–28.05%) (Agouti et al, 2007 ; Agouti, Badens, et al, 2008 ; Lemsaddek et al, 2003 , 2004 ), in Algeria (26%–43%) (Abdaoui et al, 2019 ; Bennani et al, 1994 ; Boudrahem‐Addour et al, 2009 ; Labie et al, 1990 ) and in Tunisia (49%–37.50%) (Chouk et al, 2004 ; Fattoum et al, 2004 ; Sahli et al, 2016 ). The second particularity in our result concern the three variants (FSC8(−AA), IVS‐I‐6(T > C), and IVS‐II‐745(C > G)) described in previous studies as three of the five most common variants in Morocco, are surprisingly absent in the Eastern region of Morocco and are rare in Algerian and Tunisian population.…”
Section: Discussionmentioning
confidence: 99%
“… Notes : a: (Lemsaddek et al, 2004 ), b: (Lemsaddek et al, 2003 ), c: (Agouti et al, 2007 ), d: (Agouti, Badens, et al, 2008 ), e: (Boudrahem‐Addour et al, 2009 ), f: (Abdaoui et al, 2019 ), g: (Fattoum et al, 2004 ), h: (Sahli et al, 2016 ). Bold indicates p value less than .05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high consanguinity rate among the affected was noted, and a total of 13 β‐thal mutations were identified. The mutation spectrum revealed a great molecular heterogeneity in Tunisia, with more than 28 different alleles reported to date (Chouk et al., ; Sahli et al., ).…”
Section: Hemoglobinopathies and Other Blood Disordersmentioning
confidence: 99%